Peran Kantor Urusan Agama dalam Optimalisasi Pengelolaan Wakaf - Anwar, Ali; Nasrullah, Aan; Iswanto, Juni (Kartika: Jurnal Studi Keislaman, 2024)
Waqf is an essential practice in Islam that allows the waqf of property or assets for public or religious purposes. From a historical perspective, waqf has been used in Muslims' economic and social development since the time of the Prophet. Although the concept of waqf is not explicitly mentioned in the Qur’an, it is reinforced by hadith, which underlines the underlying values of goodness, usefulness, and worship. Indonesia has laws and regulations that regulate the laws and procedures for implementing waqf, and the Office of Religious Affairs (KUA) plays an essential role in the administration and management of waqf assets. In the contemporary era, innovation and productive management of waqf assets have helped improve the welfare of society and the progress of Muslims in various countries, such as Saudi Arabia and Malaysia. Waqf remains essential in developing the economy and supporting social needs within a religious framework.